2019
DOI: 10.1253/circj.cj-19-0535
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Uninterrupted Periprocedural Edoxaban in Patients Undergoing Catheter Ablation for Atrial Fibrillation ― The Prospective KYU-RABLE Study ―

Abstract: Background: The KYU-RABLE study, a prospective, multicenter, single-arm interventional study, evaluated the efficacy and safety of uninterrupted oral edoxaban in patients undergoing catheter ablation (CA) for atrial fibrillation (AF). Methods and Results: We enrolled patients with AF from 23 centers in Japan. Edoxaban 60 mg (30 mg in patients indicated for dose adjustment) was administered uninterrupted, once daily in the morning for ≥4 weeks before CA and 4 weeks ±7 days after CA with one dose delayed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 16 publications
8
39
0
Order By: Relevance
“…In a single‐arm observational study of patients with AF, Takahashi et al showed the efficacy and safety of uninterrupted EDX administered once in the morning, with one dose delayed on the procedural day. The results showed a low composite incidence of thromboembolism and major bleeding (0.2%) 21 . Hirao et al reported that administration of rivaroxaban within 8 hours prior to the CA procedure was associated with a higher incidence of major bleeding than administration 8‐28 hours prior to the CA procedure (18% vs 0%, respectively, P = .026) 22 .…”
Section: Discussionmentioning
confidence: 98%
“…In a single‐arm observational study of patients with AF, Takahashi et al showed the efficacy and safety of uninterrupted EDX administered once in the morning, with one dose delayed on the procedural day. The results showed a low composite incidence of thromboembolism and major bleeding (0.2%) 21 . Hirao et al reported that administration of rivaroxaban within 8 hours prior to the CA procedure was associated with a higher incidence of major bleeding than administration 8‐28 hours prior to the CA procedure (18% vs 0%, respectively, P = .026) 22 .…”
Section: Discussionmentioning
confidence: 98%
“…The calculation of the target sample size was previously reported. 14 Between-group differences in baseline variables were calculated the anticipated last dose ablation duration was 30 hours, and this was subsequently refined to the four stated categories based on the number of patients and the information collected. All statistical analyses were performed using SAS 9.4 (SAS Institute Inc, Cary, NC, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, edoxaban was administered in the morning for 4 weeks ± 7 days. 14 The study was approved by the ethics committee of Oita…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the safety of edoxaban in this issue, Takahashi, et al previously performed an excellent, relatively large, prospective edoxaban single‐arm study, that is, the KYU‐RABLE study 5 . In this study, only one major bleeding complication (cardiac tamponade during the procedure: 0.2%), clinically relevant non‐major bleeding events in 1.4%, and minor bleeding events in 1.9% were observed in the 537 enrolled patients.…”
mentioning
confidence: 96%